The Influence of the School Principle's Leadership, Supervision System, and Teacher Performance on the Quality of Education at State Junior High School, Solok, West Sumatra - Nelrita; Ade Tutty R. Rossa; Sofyan Sauri; Adjat Sudrajat (GoAcademica Research & Publishing, 2022)
This study aims to determine the influence of the Principal's Leadership, Supervision System, Teacher Performance on the Quality of Education in Solok City Public Middle School, West Sumatra. This research was conducted using a quantitative approach to the survey method in the form of a descriptive study. A sample of 100 teachers were randomly selected from 6 junior high schools in 2 sub-districts. Data collection was carried out by distributing questionnaires. Data analysis using descriptive statistical methods, multiple correlation coefficients, and regression analysis with the help of SPSS version 25. This research was conducted from 28 July to 14 August 2020. All data was processed using the social science package statistical model (SPSS). Respondents are teachers who teach at State Junior High Schools in Solok City, West Sumatra. A proportional simple random sampling was taken and 100 questionnaires were completed. This questionnaire explores four variables. This study uses three structural models. The first structural model of the research results shows that there is a significant influence. So the research concluded that there is a positive effect of the leadership of the school principal on the quality of education of 0.273, there is a positive effect of the supervision system on the quality of education of 0.338, there is a positive effect of teacher performance on the quality of education of 0.405, t he second structural model is the result of the study shows the positive influence of the principal's leadership on teacher performance of 0.320, there is an influence of the supervision system on teacher performance of 0.202. The third structural model of the research results has a positive influence of the principal's leadership on supervision of 0.417. The results of this study show the important role of the teacher in improving the quality of education. But the three variables are interrelated and play a role in improving the quality of education.